Unexplored Directions in Spoken Language Technology for Development - Weber, Frederick; Bali, Kalika; Rosenfeld, Roni; Toyama, Kentaro (Proceedings of The 2nd IEEE Workshop on Spoken Language Technology. 2008, 2008)
The full range of possibilities for spoken-language technologies (SLTs) to impact poor communities has been investigated only partially, despite what appears to be strong potential. Voice interfaces raise fewer barriers for the illiterate, require less training to use, and are a natural choice for applications on cell phones, which have far greater penetration in the developing world than PCs. At the same time, critical lessons of existing technology projects in development still apply and require careful attention. We suggest how to expand the view of SLT for development, and discuss how its potential can realistically be explored.